2012
DOI: 10.1016/j.intimp.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic efficacy of Ulinastatin for rats with smoking inhalation injury

Abstract: Smoke inhalation injury represents a major cause of mortality in burn patients and is associated with a high incidence of pulmonary complications. Ulinastatin (UTI) has been widely used as a drug for patients with severe burn, sepsis, severe acute pancreatitis, and multiple organ dysfunction syndrome. In view of the critical role of inflammatory response in pathogenesis of smoke inhalation-induced lung injury and the anti-inflammatory effects of UTI, we hypothesized that treatment with UTI could lessen smoke i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The second finding of this study is that UTI is also an effective anti‐inflammatory agent against allergic inflammation. Previous studies have reported that UTI protected against neutrophil‐mediated inflammation and organ injury (Masuda et al ., ; Inoue et al ., 2005a,b; Molor‐Erdene et al ., ; Takano et al ., ; Koga et al ., ; Qiu et al ., ; Rui et al ., ). However, the effect of UTI on allergic inflammation has not been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second finding of this study is that UTI is also an effective anti‐inflammatory agent against allergic inflammation. Previous studies have reported that UTI protected against neutrophil‐mediated inflammation and organ injury (Masuda et al ., ; Inoue et al ., 2005a,b; Molor‐Erdene et al ., ; Takano et al ., ; Koga et al ., ; Qiu et al ., ; Rui et al ., ). However, the effect of UTI on allergic inflammation has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous administration of UTI to endotoxaemic animals inhibited inflammatory mediator production, reversed systemic hypotension (Molor‐Erdene et al ., ), prevented intravascular coagulation (Takano et al ., ) and ameliorated multiple organ injury (Takano et al ., ; Zhang et al ., ). UTI protected against ischaemia‐reperfusion (Yano et al ., ; Koga et al ., ), haemorrhage (Masuda et al ., ), smoke inhalation (Qiu et al ., ) or organ injury induced by sea water inhalation (Rui et al ., ). UTI has also been shown to have beneficial effects in patients with severe sepsis, traumatic brain injury and acute Kawasaki disease (Chen et al ., ; Kanai et al ., ; Tu et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The activation of NF-κB is regulated via cytoplasmic sequestration of NF-κB by the inhibitor of κB (IκBs) family of proteins (Qiu et al, 2012). IκB-α, one isoform of IκBs, can sequester NF-κB in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, puerarin could attenuate pathological changes and protect rats against immune-mediated lung injury. As a histological hallmark of ALI/ARDS, local accumulation of neutrophils in lung parenchyma is implicated in the pathophysiology of ALI induced by smoke inhalation, lipopolysaccharide, radiation and ischemiareperfusion injury; and investigation of BALF from patients with ARDS has shown excess numbers of neutrophils, which produce excessive amounts of pathogenic factors such as protease and elastase [19,[23][24][25]. Consistent with previous studies, our results showed that neutrophils were significantly increased in BALF after smoke inhalation, but were decreased by administration of puerarin.…”
Section: Discussionmentioning
confidence: 99%